Pengaruh Pengungkapan Sustainability Report terhadap Nilai Perusahaan Manufaktur yang Terdaftar di Bei Periode 2020-2022 - Nova Eroka Rossa (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to determine the effect of sustainability reports on company value in manufacturing companies listed on the Indonesia Stock Exchange. The sustainability report has 6 measurements, namely economic, environmental, labor, human rights, social and product disclosures. This study had a sample of 90 and was measured using multiple linear regression analysis using the SPSS version 26 application. The research results showed that there was an influence on the disclosure of economic, environmental, labor, human rights, social and product sustainability reports on company value.